2015
DOI: 10.1021/jp510743h
|View full text |Cite
|
Sign up to set email alerts
|

Design of SrTiO3-Based Thermoelectrics by Tungsten Substitution

Abstract: Among n-type oxide thermoelectrics, donor-substituted strontium titanates, prepared in highlyreducing conditions, show particularly attractive thermoelectric figure of merit. High electrical conductivity, combined with outstanding redox tolerance and perovskite-phase stability of these materials, also make them prospective candidates for SOFC anode components. This work represents a first attempt to process strontium titanate ceramics with significant W for Ti substitution, and to assess their relevant defect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 66 publications
1
19
0
Order By: Relevance
“…These point defects play a crucial role in reducing thermal conductivity by scattering of phonons. 15,[17][18][19] Various cationic substitution have been reported for Sr and Ti sites to improve the electrical conductivity, with predominately lanthanides on Sr sites 20,21 and transition metals (Nb, 22 W, 23 Ta, 7,24 Y 25 ) on Ti sites. These investigations have improved the understanding of the interrelationship between different correlated variables and pushed the ZT values for SrTiO 3 based polycrystalline materials up to 0.35 to 0.41 at 1000 K. 20,26,27 We recently reported that the introduction of metallic inclusion such as Fe and Cu improved the thermoelectric properties of the base material.…”
Section: Introductionmentioning
confidence: 99%
“…These point defects play a crucial role in reducing thermal conductivity by scattering of phonons. 15,[17][18][19] Various cationic substitution have been reported for Sr and Ti sites to improve the electrical conductivity, with predominately lanthanides on Sr sites 20,21 and transition metals (Nb, 22 W, 23 Ta, 7,24 Y 25 ) on Ti sites. These investigations have improved the understanding of the interrelationship between different correlated variables and pushed the ZT values for SrTiO 3 based polycrystalline materials up to 0.35 to 0.41 at 1000 K. 20,26,27 We recently reported that the introduction of metallic inclusion such as Fe and Cu improved the thermoelectric properties of the base material.…”
Section: Introductionmentioning
confidence: 99%
“…Tungsten is interesting as it can donate two electrons per W cation and also scatters the phonons due to mass fluctuation in STO. While a ZT of 0.24 was reached at 1300 K by substituting 0.06 portion of W, on codoping W and Nb in STO (Sr 0.97 Ti 0.8 Nb 0.17 W 0.03 O 3±δ ) resulted in a ZT of 0.28 at 1270 K. Better performance due to Nb codoping was assigned to the phase separation and phonon scattering [25]. Kovalivisky et al reported the effect of Pr substitution.…”
Section: Srtiomentioning
confidence: 99%
“…Special attention should be paid for double alloying of SrTiO 3 -based thermoelectrics. Diversity of dissipation sites in the crystal lattice always enhances thermal conductivity reduction κ : (Sr 1−x−y La x Yb y )TiO 3 [61], Sr 1−x (Ti 1−y−z Nb y W z )O 3±δ [62], (Sr 1−x La x )(Ti 1−x Ta x )O 3 and (Sr 1−x La x )(Ti 1−x Nb x )O 3 [63]. On the other hand, conductivity and Seebeck’s coefficient are also affected in a way depending on the quantity and/or the type of point defects.…”
Section: Theoretical Aspects Of Thermoelectricitymentioning
confidence: 99%